Why do central banks make public announcements of open market operations? - Narayan Bulusu (Bank of Canada, 2020)
Central banks make public the results of open market operations (OMOs), which they use to adjust the liquidity available to the financial system to maintain the short-term borrowing rate in the range compatible with achieving their monetary policy objectives. This paper shows that such announcements are costly because they moderate the impact of changes in supply achieved through OMOs. Nevertheless, communication of OMOs is desirable because it improves the transparency of the funding market, which makes the price of liquidity - a key input into economic decision making - more reflective of underlying demand and supply of liquidity.
Keywords: D52; E58; G21; 330; Central bank research; Monetary policy implementation